Digital Assets: Legal Regulation and Estimation of Risks - S. V. Muradyan (Journal of Digital Technologies and Law, 2023)
Objective: to substantiate the need to create a universal mechanism of legal regulation of digital currencies and tokenized assets, based on a uniform categorization of digital assets and the author’s interpretation of the conception of digital assets risk, in order to ensure their safe circulation with legal means and effective development of the global digital economy in the future.Methods: the research was carried out with a combination of cognition techniques of various levels: from philosophical to private scientific; the key position among them belongs to a systemic approach, a comparative legal method and a formal-juridical analysis of normative materials.Results: the present research lays the conceptual basis for building a global system of legal regulation of digital assets circulation and facilitates identifying and resolving the key issues, necessarily emerging in the analysis of the current mechanisms of legal regulation at national level and in the estimation of various types of digital assets.Scientific novelty: consists in a comprehensive consideration of the essence and features of the legal nature of various types of digital assets, possessing, alongside with significant advantages, high risks from legal and financial viewpoints. Based on contradictory approaches and revealed gaps in the legal regulation of various types of digital assets, the author proposes a uniform categorization of digital assets, substantiates the concept of digital assets risk, attempts to substantiate the need to create a universal mechanism of legal regulation of digital currencies and tokenized assets, which would allow forming an effective system of means to protect property right to them and ensure safety of their circulation.Practical signiﬁcance: is due to the current absence of a unified approach and a possibility to apply the existing legal norms in relation to innovative digital assets, taking into account their specificity, despite their trans-border character. The main provision and conclusions of the research can be used to improve the mechanisms of legal regulation of digital assets circulation.